Local Voices in Creative Writing - Harris Hermansyah Setiajid (Bandar Lampung University (UBL), 2014)
Creative writing is now on the centre stage in the world literary discourse. Beside other numerous advantages, the creative writing is also used to put forward the unheard voices hidden in the mainstream literary works. In the recent development, creative writing is also a means to unearth the local voices in order to be put in a world stage, introduced to a larger audience to achieve a better understanding between cultures.Since creative writing is no longer locked in the three literary genres, namely poetry, prose, or drama, the teaching of creative writing in university classrooms needs reorienting. Traditionally, creative writing is taught within a relatively strict prescribed formula. The students have a limited freedom in terms of the format and the content. This paper tries to present the experiment done in a creative writing classroom which applies unorthodox teaching method of creative writing. The result is somewhat beyond expectation, the students are able to write fluently with more diverse issues, covering from political to cultural ones.The method is also able to uncover the local voices which are hidden and sometimes deliberately forgotten.